Challenging the Biginelli scaffold to surpass the first line antitubercular drugs: Mycobacterium tuberculosis thymidine monophosphate kinase (TMPKmt) inhibition activity and molecular modelling studies - Mai S. El-Shoukrofy; Amal Atta; Salwa Fahmy; Dharmarajan Sriram; Michael G. Shehat; Ibrahim M. Labouta; Mona A. Mahran (Journal of Enzyme Inhibition and Medicinal Chemistry)
New Biginelli adducts were rationalised, via the introduction of selected anti-tubercular (TB) pharmacophores into the dihydropyrimidine (DHPM) ring of deoxythymidine monophosphate (dTMP), the natural substrate of Mycobacterium tuberculosis thymidine monophosphate kinase (TMPKmt). Repurposing was one of the design rationale strategies for some selected mimics of the designed compounds. The anti-TB activity was screened against the Mtb H37Rv strain where 11a was superior to ethambutol (EMB), and was 9-fold more potent than pyrazinamide (PZA). Additionally, compounds 11b, 4a, 4b, 13a, 13b and 14a elicited higher anti-TB activity than PZA, showing better safety profiles than EMB against RAW 264.7 cells’ growth. The in vitro TMPKmt inhibition assay released compounds 11a, 11b and 13b as the most potent inhibitors. Docking studies presumed the binding modes and molecular dynamics (MD) simulation revealed the dynamic stability of 11a-TMPKmt complex over 100 ns. In silico prediction of the chemo-informatics properties of the most active compounds was conducted.